-6p-14=2-4p

Simple and best practice solution for -6p-14=2-4p equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6p-14=2-4p equation:



-6p-14=2-4p
We move all terms to the left:
-6p-14-(2-4p)=0
We add all the numbers together, and all the variables
-6p-(-4p+2)-14=0
We get rid of parentheses
-6p+4p-2-14=0
We add all the numbers together, and all the variables
-2p-16=0
We move all terms containing p to the left, all other terms to the right
-2p=16
p=16/-2
p=-8

See similar equations:

| -2(.25s)-5+3=3 | | 0.2(30x-10)=15 | | 4(z-8)-6=10 | | 2x+(-3x-10)=-154 | | -2-7n=-8n+8-4 | | 6=a+2a | | 2(1+7x)-1=-27+7x | | -18=3x=6 | | 180=-4(-3+7m) | | 9(z-3)=122 | | 7y-8y-9=10 | | -4(8)-5n=13 | | 3x-5(x+8)=-16-5x | | 6y/5+3/5=0 | | 36000+2000x=30000+2400x | | (1/3)*b=25 | | 3p-1=4p | | (1/3)b=25 | | 18x=7/6 | | 23-17k-1=-2k+367 | | 11=1+6v+4v | | N+3+2n=18 | | 4(5n+7)-3n=12n-27 | | 2x+9/8=14 | | 5x-4x=-2+7 | | 12-6/2x3=11 | | -90+x=53-12x | | 12-3n=10-2n | | 6n-2n=-24 | | 4x^+2x=0 | | 4x−9+19=8x−14 | | 33=p-67.71 |

Equations solver categories